Dissipation characteristics and safety evaluation of spinetoram in red bayberry and soil - WANG Tianyu; LIN Mei; YAO Zhoulin; WANG Peng; PING Xinliang; FANG Hua (浙江大学学报. 农业与生命科学版)
To assess the environmental safety of applications of insecticide spinetoram in red bayberry, the analytical method and residue dynamics as well as final residues in the red bayberry and soil were investigated in Zhejiang and Fujian for two years. The plant samples were extracted with acetonitrile, cleaned up with primary secondary amine (PSA) sorbent and anhydrous magnesium sulfate, and analyzed by ultra performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). The soil samples were extracted with water-acetonitrile, cleaned up with PSA sorbent and analyzed by UPLC-MS/MS, and quantified by external standard method. The results showed good linearity (R2＞0.999) between concentration and peak area when the concentrations of spinetoram ranged from 0.001 to 0.5 mg/L. When the spiked levels ranged from 0.005 to 0.5 mg/kg, the average recoveries in the red bayberry were in the range of 89.40% to 101.85%, with relative standard deviations (RSDs) of 3.63%-7.25%; the average recoveries in the soil were in the range of 95.09% to 102.66%, with RSDs of 3.05%-3.61%; the limit of detection (LOD) was 5.2×10－5 mg/kg, while the limits of quantification (LOQs) were 5.0×10－3 mg/kg for the red bayberry and soil. When the red bayberry was sprayed with 60 mg/L spinetoram suspension concentrate at the 1.5 times of the recommended maximum dosage at fruit color-changed period (one time), the dissipation dynamics of spinetoram in the red bayberry and soil were in accordance with the first-order kinetic equation, and the dissipation half lives of spinetoram residues were 4.4-5.2 and 1.2-1.9 d in the red bayberry and soil, respectively, belonging to degradable pesticide. The final residues were 0.073-0.353 mg/kg in the red bayberry and less than the limit of quantification-0.094 mg/kg in the soil at 7 d after spraying. In conclusion, the methods are fast, accurate and sensitive for detection of spinetoram residues in the red bayberry and soil, and the dissipation half lives of spinetoram are short after using the concentration and times recommended by the field experiment, and the final residues are lower than the maximum residue limit of red bayberry stipulated by national standard (1 mg/kg). Therefore, it is safe to use spinetoram for the pest control of red bayberry tree in preharvest interval.